MODEL PERSAMAAN STRUKTURAL TINGKAT KEPUASAN PASIEN PADA KUALITAS LAYANAN RAWAT INAP - APRIYANI, LIA; KENCANA, EKA N.; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 6 No 3 (2017)DO - 10.24843/MTK.2017.v06.i03.p162, 2017)
Satisfaction level on inpatient service is determined by several factors such as the perceived quality about nursing and/or medical services. This study is directed to determine those factors that affect the satisfaction level of the patient families regarding the quality of inpatient service in one public hospital at Denpasar City of Bali. The data from 150 families who utilised inpatient services were collected by using a self-administered questionnaire and were analysed by applying factor analysis to extract the influential factors. In addition, the causal relationship among factors were studied by utilising partial least squares structural equation modeling (PLS-SEM). Factor analysis confirmed there are five influential factors in determining quality of services, i.e. attention, tangible aspects, assurance, reliability, and responsiveness. By positioning these factors as the exogenous and quality of inpatient services as the endogenous one, we found all factors had determination power as much as 36.6 percent. Furthermore, the satisfaction level regarding the quality of inpatient service had been significantly affected as much as 0.917 with the coefficient of determination’s value is 84.0 percent.